2021
DOI: 10.1097/ccm.0000000000005315
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdynamic Left Ventricular Ejection Fraction in ICU Patients With Sepsis

Abstract: To evaluate the cause and prognosis of hyperdynamic left ventricular ejection fraction in critically ill patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 27 publications
2
39
1
1
Order By: Relevance
“…Several studies have confirmed the high mortality rate in patients with sepsis, ranging from 34 to 56% (5) and 33.5% (6) in foreign and domestic countries, respectively, and even higher in patients with combined hyperdynamic left ventricular function or myocardial depression (3,7). Standardizing the staging of myocardial depression in sepsis and realizing the early identification of patients with sepsis are of great significance for clarifying the cardiac changes in sepsis at various stages, adjusting and guiding treatment in a timely manner, and optimizing hemodynamics.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have confirmed the high mortality rate in patients with sepsis, ranging from 34 to 56% (5) and 33.5% (6) in foreign and domestic countries, respectively, and even higher in patients with combined hyperdynamic left ventricular function or myocardial depression (3,7). Standardizing the staging of myocardial depression in sepsis and realizing the early identification of patients with sepsis are of great significance for clarifying the cardiac changes in sepsis at various stages, adjusting and guiding treatment in a timely manner, and optimizing hemodynamics.…”
Section: Discussionmentioning
confidence: 94%
“…Our murine model was calibrated to ensure systemic inflammation and lack of hypovolaemia without mortality. Hyperdynamic physiology appears to be an independent predictor of mortality independent of preload as a likely contributory factor [ 5 ]. Although impaired left ventricular relaxation may also reduce preload, diastolic dysfunction appears to be common when myocardial contractility is depressed in sepsis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperdynamic physiology appears to be an independent predictor of mortality independent of preload as a likely contributory factor [ 5 ]. Although impaired left ventricular relaxation may also reduce preload, diastolic dysfunction appears to be common when myocardial contractility is depressed in sepsis [ 5 ]. By using a model where surgery (such as caecal ligation and puncture) requiring anaesthesia could be avoided, further confounding factors that may have blurred sex-specific differences in previous studies were minimised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-seven percent of our cohort had hyperdynamic LV ejection fraction (HDLVEF), and this should not be considered “normal.” The prevalence of HDLVEF was higher in nonsurvivors than that in survivors (46% vs 32%). Although HDLVEF is associated with poor prognosis in critically ill patients with sepsis ( 4 ), likely due to unmitigated vasoplegia precipitating a high cardiac output state, in ARDS, its development may be due to low LV preload, caused by RV systolic impairment and/or obstruction of LV filling from RV dilation (RVD). HDLVEF may, therefore, reflect a low cardiac output state that precipitates multiple organ dysfunction and death.…”
mentioning
confidence: 99%